Pengaruh Pemberian Terapi Kompres Blue Ice Gel Terhadap Penurunan Intensitas Nyeri Pada Bayi Sebelum Imunisasi - Sari, Winda; Jasmawati, Jasmawati; Raihanah, Siti (Bunda Edu-Midwifery Journal (BEMJ), 2023)
Vaccination is an effort to improve the health of infants and young children. This procedure requires the baby to be pricked with a needle and causes pain. The psychological consequences that occur when a child feels pain are phobias and stress. Non-medical treatment in the form of blue ice gel packs can reduce pain. In the work area of ​​Lok Bahu Health Center, the aim is to conduct a study to determine the effect of blue ice gel packs on reducing pain intensity in babies before vaccination. A methodological study is a quasi-experiment involving only a post-test with a control group design. The study sample included all infants older than 2 months in the working area of ​​Lok Bahu Health Center, with a total of 18 in each group using a random sampling technique. The independent variable is Compress Blue Ice Gel and the dependent variable is the intensity of the babies' pain. The research instruments are Blue Ice Gel Compress SOP and FLACC Scale. The statistical test used is the Kolmogorov-Smirnov test. Results of the study Kolmogorov-Smirnov test results obtained Pvalue 0,000 less than